YTHDF2, a protein repressed by miR-145, regulates proliferation, apoptosis, and migration in ovarian cancer cells - Jie Li; Lei Wu; Meili Pei; Yun Zhang (BMC, 2020)
Abstract RNA methylation can reverse the methylation modification at the RNA level, which is an extremely important epigenetic modification. The function and mechanism of YTHDF2, as a reader of m6A modification, in epithelial ovarian cancer (EOC) have not been elucidated so far. This study aimed to investigate how YTHDF2 and miR-145 modulated EOC progression through m6A modification. It demonstrated that YTHDF2 was significantly upregulated in EOC tissues compared with normal ovarian tissues. Further functional studies confirmed that YTHDF2 significantly promoted the proliferation and migration of EOC cell lines and reduced the global 6-methyladenine (m6A) mRNA levels. Next, the expression levels of miR-145 and YTHDF2 were found to be inversely correlated in ovarian cancer tissues and cells, and YTHDF2 was the direct target gene of miR-145. A crucial crosstalk occurred between miR-145 and YTHDF2 via a double-negative feedback loop. The overexpression of YTHDF2 rescued miR-145-induced reduction of the proliferation and migration of EOC cells. Hence, YTHDF2 and miR-145, as two crucial m6A regulators, were involved in the progression of EOC by indirectly modulating m6A levels. The findings of this study on YTHDF2 and miR-145 might provide new insights into carcinogenesis and new potential therapeutic targets for EOC.